Poverty profiles and well-being: Panel evidence from Germany - Andrew E. Clark; Conchita D'Ambrosio; Simone Ghislandi (Deutsches Institut für Wirtschaftsforschung (DIW), 2015)
We consider the link between poverty and subjective well-being, and focus in particular on the role of time. We use panel data on 49,000 individuals living in Germany from 1992 to 2012 to uncover three empirical relationships. First, life satisfaction falls with both the incidence and intensity of contemporaneous poverty. Second, poverty scars: those who have been poor in the past report lower life satisfaction today, even when out of poverty. Last, the order of poverty spells matters: for a given number of years in poverty, satisfaction is lower when the years are linked together. As such, poverty persistence reduces well-being. These effects differ by population subgroups.
Keywords: I31; I32; D60; 330; income; poverty; subjective well-being; SOEP